TELAAH KURIKULUM 2013 MENURUT FILSAFAT PROGRESIVISME - Nuraeningsih Nuraeningsih; Wening Sahayu (Universitas Muria Kudus, 2022)
The purpose of this study is to analyze the philosophical foundations of the 2013 curriculum in relation to 21st century skills. The research method used is a literature study that examines the 2013 Curriculum from a review of the philosophy of progressivism. The data collected is in the form of books, articles and relevant research on the 2013 Curriculum and the flow of progressive philosophy. The method of analysis is carried out by means of the description method and the critical method. Through the description method, the data obtained is studied in depth supported by previous research that has relevance to the theme. The collected data is then analyzed and interpreted. Furthermore, the results of the analysis are drawn conclusions as an answer to the problem. The results of the analysis show that the philosophy of progressivism education underlies the 2013 curriculum which is characterized by student-centered learning which encourages students to actively explore to develop their attitudes, knowledge and skills.